Przemilczana rocznica. Czterechsetlecie wydania Memoriału frankfurckiego - Sarnecki, Robert (Biuletyn Historii Wychowania, 2013)
In 1613, the German linguist Wolfgang Ratke presented to the parliament assumptions, which later became the basis for the development of the system of teaching. Pioneering the views of the organizations concerned by the learning process. He drew attention to the need for education in accordance stages of human development, called for education in the national language. The foundations of teaching principles gradation of difficulty. His views were not initially accepted mino positive reviews J. Jung and K. Helwig, who expressed appreciation for the progressive thinking of Wolfgang Ratke. It took 400 years from the moment the first time the name was used teaching. The analysis of available sources indicates that contemporary educators did not pay the anniversary of interest.